2015
DOI: 10.1128/mbio.00775-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Klebsiella pneumoniae Fitness Genes during Lung Infection

Abstract: Klebsiella pneumoniae is an urgent public health threat because of resistance to carbapenems, antibiotics of last resort against Gram-negative bacterial infections. Despite the fact that K. pneumoniae is a leading cause of pneumonia in hospitalized patients, the bacterial factors required to cause disease are poorly understood. Insertion site sequencing combines transposon mutagenesis with high-throughput sequencing to simultaneously screen thousands of insertion mutants for fitness defects during infection. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
231
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(255 citation statements)
references
References 37 publications
9
231
0
Order By: Relevance
“…While our work demonstrates urinary Cu mobilization via ceruloplasmin during UTI with Gram-negative pathogens, whether the Cu mobilization response is conserved during UTI with Gram-positive pathogens remains to be examined. Mutants lacking Cu detoxification systems in diverse pathogens, including Cryptococcus neoformans (a fungus), K. pneumoniae, Mycobacterium tuberculosis, Salmonella enterica serovar Typhimurium, Streptococcus pneumoniae, and UPEC, are attenuated in animal models of infection (11,(26)(27)(28)(29)(30)(31). Our results presented here elucidate the protective role of Cu in the pathogenesis of UTI.…”
Section: Discussionmentioning
confidence: 68%
“…While our work demonstrates urinary Cu mobilization via ceruloplasmin during UTI with Gram-negative pathogens, whether the Cu mobilization response is conserved during UTI with Gram-positive pathogens remains to be examined. Mutants lacking Cu detoxification systems in diverse pathogens, including Cryptococcus neoformans (a fungus), K. pneumoniae, Mycobacterium tuberculosis, Salmonella enterica serovar Typhimurium, Streptococcus pneumoniae, and UPEC, are attenuated in animal models of infection (11,(26)(27)(28)(29)(30)(31). Our results presented here elucidate the protective role of Cu in the pathogenesis of UTI.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, it is important to remember that the majority of people presenting with K. pneumoniae pneumonia and bacteremia are in hospitals or long-term-care facilities and are immunosuppressed in some manner. Many of the recent searches for virulence factors have focused on identifying virulence factors in "normal" mice; however, a subset of these factors may not be required in immunosuppressed environments (363). In fact, different genes may play a role in immunosuppressed patient subsets that have yet to be identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a preliminary characterization of 6 of these genes found that they appear to be important for virulence by playing either a protective role against the immune response or a role in the acquisition of resources. Specifically, those authors found that rfaH promoted serum resistance and capsule production, aroE promoted serum resistance, ilvC and ilvD were important for branched-chain-amino-acid synthesis, and copA promoted resistance to copper toxicity (363).…”
Section: New Genetic Screens To Identify More Putative K Pneumoniae mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors then used transposon-directed insertion site sequencing to identify approximately 400 genes that were essential for growth of C. difficile in vitro and 798 genes that participate in C. difficile sporulation. In a separate study, more than 25,000 random insertion mutants were generated in the Klebsiella pneumniae reference strain KPPR1 and genes that participate in establish lung infection in a mouse model were identified by comparing the relative abundance of mutants in the initial inoculum and in the lung after infection [55]. This study identified more than 300 genes that resulted in at least a two-fold reduction in abundance in lung tissue when compared to the inoculum, and 69 genes with at least a 10-fold decrease in abundance.…”
Section: Essential Genes As Targets For Antibiotic Discoverymentioning
confidence: 99%